Penghimpunan Dana Nasabah dengan Akad Wadi’ah dan Penerapannya pada Perbankan Syariah - Dalimunthe, Nikmah; Pane, Jihan Atiqah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to determine the systematic collection of customer funds in Islamic banking using wadi’ah contracts. In the main activities of the Banking as a financial intermediary institution because it collects funds from the public in the form of savings. In the implementation of banking activities using contracts that are in accordance with the Shari’a. One of the contracts that protect the customer’s assets is called a wadiah contract. In this contract, the customer’s funds deposited with the bank will receive a safe guarantee, and Islamic banking is obliged to bear all risks that occur in customer funds. Furthermore, not only guarantees, but Islamic banking will also provide benefits to these customers with a profit-sharing system. Wadi’ah in principle is to help the custodian, and the party entrusted with its position as a helping party. Therefore, the nature of wadi’ah is trust. In general, there are two types of wadi’ah, wadi’ah yad al-amanah and wadi’ah yad dha-manah. The method used in this research is qualitative with library study data collection methods based on book review techniques, literature searches, notes, and reports related to research. This study describes how the mechanism of Islamic banking in collecting customer funds in the bank by using wadiah contracts. Is the collection of customer funds in accordance with Islamic sharia regulations.